THE CRIMINAL RESPONSIBILITY FOR PORNOGRAPHY VIDEO MAKER THROUGH DIGITAL FORENSICS ON SOCIAL MEDIA - Hartono, Dhimas Joeantito; Sugiharto, Dr. (jfpublisher, 2022)
Cybercrime phenomenon is a crime that is not easy to trace its existence. Digital Forensics is an application in the Computer Science and Technology for the purpose of pro-justice, which in this case is to prove scientifically high-tech crimes so that digital evidence is obtained and it can be used to catch pornography suspects, which was transmitted to various media, such as magazines, television programs, and internet. Cyberporn is a crime in transmitting some pornography contents through website. This research used juridical- normative method as its research method. The researcher used the method to find out the criminal responsibility for pornography video maker through digital forensics on social media. In consequence, if there is a punishment for the perpetrator, then it is retaliation for his actions which aims to improve attitudes and behavior so that they are even better in using social media services and are also intended to prevent others from the possibility of committing similar acts.